2020
DOI: 10.1213/ane.0000000000004515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Carbohydrate Intake During Labor on the Rate of Instrumental Vaginal Delivery: A Multicenter, Randomized Controlled Trial

Abstract: BACKGROUND: Carbohydrate intake during physical exercise improves muscle performance and decreases fatigue. We hypothesized that carbohydrate intake during labor, which is a period of significant physical activity, can decrease the instrumental vaginal delivery rate. METHODS: In a multicenter, prospective, randomized, controlled trial, healthy adult pregnant women presenting with spontaneous labor were assigned to a “Carbohydrate” group (advised to drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
2
1
Order By: Relevance
“…Although the calorie intake in the carbohydrate-rich group would be high enough to prevent ketosis as well, we could find rate differences of neither cesarean delivery nor forceps delivery. Similar results were also reported by others comparing low-carbohydrate drinks vs. none-carbohydrate drink or food intake vs. fasting/water drink [ 14 , 17 20 , 40 , 41 ]. Thus, taken together, it seems that the content of carbohydrate supplementation does not change mode of delivery.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although the calorie intake in the carbohydrate-rich group would be high enough to prevent ketosis as well, we could find rate differences of neither cesarean delivery nor forceps delivery. Similar results were also reported by others comparing low-carbohydrate drinks vs. none-carbohydrate drink or food intake vs. fasting/water drink [ 14 , 17 20 , 40 , 41 ]. Thus, taken together, it seems that the content of carbohydrate supplementation does not change mode of delivery.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the overall rate of vomiting during labor was 10.9%, lower than those reported in previous studies (range from 15.6 to 37%) [ 17 , 40 , 50 , 51 ]. Furthermore, the rate of vomiting was lower in the carbohydrate-rich group than in the low-carbohydrate group in our finding.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…10 The resultant extremely low incidence of aspiration means we can pay attention to the energy needs of pregnant women during labor. Some studies have found that patients with gastrointestinal dysfunction have a lower incidence of gastroesophageal re ux and vomiting after eating semi-solid food than after consuming liquids [10][11]. Consistent with the dietary culture in China, for many years most parturients have eaten semi-solid food during labor [12].…”
Section: Discussionmentioning
confidence: 93%